Candidate genes involved in cuticular hydrocarbon differentiation between cryptic, parabiotic ant species. Issue 5 (17th March 2021) - Sprenger, Philipp P; Hartke, Juliane; Schmitt, Thomas; Menzel, Florian; Feldmeyer, Barbara
Abstract: Insect cuticular hydrocarbons (CHCs) are highly diverse and have multiple functions, including communication and waterproofing. CHC profiles form species-specific, complex blends of up to 150 compounds. Especially in ants, even closely related species can have largely different profiles, raising the question how CHC differences are mirrored in the regulation of biosynthetic pathways. The neotropical ants Crematogaster levior and Camponotus femoratus both consist of two cryptic species each that are morphologically similar, but express strongly different CHC profiles. This is ideal to study the molecular basis of CHC differences. We thus investigated gene expression differences in fat-body transcriptomes of these ants. Despite common garden conditions, we found several thousand differentially expressed transcripts within each cryptic species pair. Many of these were related to metabolic processes, probably accounting for physiological differences. Moreover, we identified candidate genes from five gene families involved in CHC biosynthesis. By assigning candidate transcripts to orthologs in Drosophila, we inferred which CHCs might be influenced by differential gene expression. Expression of these candidate genes was often mirrored in the CHC profiles. For example, Cr. levior A, which has longer CHCs than its cryptic sister species, had a higher expression of elongases and a lower expression of fatty acyl- CoA reductases. This study is one of the first to identify CHC candidate genes in ants and will provide a basis for further research on the genetic basis of CHC biosynthesis.